THE THEORY OF AN INTEGRATIVE APPROACH TO THE ANALYSIS OF THE PHENOMENON OF METONYMY (Archive of Conferences, 2021)
Although the phenomenon of metonymy has been attracting the attention of scientists for many centuries, but the development of cognitive linguistics has led to a new turn in the study of this phenomenon. J. Lakoff, M. Johnson’s book Metaphors We Live by, published in 1980, led to revolutionary changes in the coverage of the nature of metaphor and metonymic phenomena. Since then, the study of the phenomenon of metonymy not limited to the field of rhetoric, but also began to cover the field of human thought activity.